Internalisasi Nilai Ubudiyah Melalui Budaya Mengaji Dalam Pembelajaran Pendidikan Agama Islam di SMK YPM 12 Tuban - Much. Machfud Arif; Khotimatus Sa’adah; Alfi Manzilatir Rohmah; Lailatul Mahmuddah (Yayasan Al-Afif, 2026)
This study examines the internalization of ubudiyah values through the culture of Qur’an recitation in Islamic Religious Education (PAI) learning at SMK YPM 12 Tuban. The background of this research is based on the tendency of PAI learning that still emphasizes cognitive aspects, so it has not fully succeeded in shaping students’ religious character. Therefore, a learning approach is needed that integrates cognitive, affective, and psychomotor aspects through value internalization. This study aims to analyze the process and impact of internalizing ubudiyah values through the culture of reciting the Qur’an. This research uses a qualitative approach with a descriptive type. Data were collected through observation, interviews, and documentation involving teachers and students as research subjects. The results show that the internalization process is carried out through stages of value transformation, value transaction, and transinternalization supported by habituation and teacher role modeling. The implementation of Qur’an recitation culture at the end of learning has proven effective in strengthening students’ understanding and appreciation of Islamic teachings. The impact of this activity includes improving students’ worship practices, discipline, emotional stability, and the formation of a religious school environment. These findings indicate that the integration of religious culture in learning can be an effective strategy in strengthening the internalization of Islamic values. The implication of this research emphasizes the importance of developing learning models based on school religious culture to support the formation of students religious characterin a sustainable manner.